Effectiveness of Sensitisation Programme on Prazosin Therapy for Scorpion Envenomation at Primary and Secondary Healthcare Level - B RAMESHBABU; P PUNITHA; E MANOCHITRA; K SASIKALA; J BALAJI (Indian Journal of Neonatal Medicine and Research, 2022)
Introduction: Scorpion envenomation is a life-threatening paediatric emergency. Prazosin-an alpha-1 blocker is the gold standard therapy for scorpion envenomation. Many children with scorpion envenomation were under-treated at Primary Healthcare (PHC) and Secondary Healthcare (SHC) level because of lack of awareness about prazosin therapy. If Prazosin is started earlier at PHC and SHC level, complications and mortality can be reduced. Aim: To conduct sensitisation programme for PHC and SHC doctors regarding the management of paediatric emergencies including scorpion envenomation, and to evaluate the effectiveness of sensitisation programme on prazosin therapy for scorpion envenomation at PHC and SHC level. Materials and Methods: This non concurrent clinical trial consisted of training PHC and SHC doctors at the Department of Paediatrics, Government Dharmapuri Medical College Hospital, Tamil Nadu, India for a period of two years (January 2018-December 2019). After the training, children aged 1 month-12 years with features of scorpion envenomation referred from PHC and SHC to this tertiary care centre, during January 2021-September 2021 were evaluated. The data regarding initiation of prazosin therapy at PHC and SHC level and the clinical profile, complications and outcome at tertiary care level were noted. The present study parameters were compared with previous study on scorpion envenomation, done before the sensitisation programme in the same centre, and the data were compared. Results: Training was given to 120 medical officers of PHC and SHC. Sixty-two children, with scorpion envenomation referred from PHC and SHC, were included in the study. Seven (10%) children were brought to the tertiary care centre directly were excluded. Prazosin therapy was initiated in 43 (69.3%) children at PHC and SHC level before referral. Initiation of prazosin within four hours of scorpion sting was done in 45 (72.6%). Common symptoms were pain {42 (68%)}, diaphoresis {26 (42%)} and salivation {25 (40%)}. Cold peripheries, myocarditis and pulmonary oedema were noted in 24 (39%), 4 (6%) and 6 (10%) children, respectively. Dobutamine and Non Invasive Ventilation (NIV) were needed in 13 (21%) and 11 (18%) cases, respectively. When compared to the observations pre-training, peripheral circulatory failure (76% to 39%) (p=0.019), pulmonary oedema (27% to 10%) (p=0.010), myocarditis (17% to 6%) (p=0.039), ionotrope support (41% to 21%) (p=0.024), and NIV (39% to 18%) (p<0.003) were significantly reduced. There was no mortality. Conclusion: Following the sensitisation programme, initiation of prazosin for scorpion envenomation at PHC and SHC level significantly improved. Complications like myocarditis, pulmonary oedema, need for inotropes and ventilator support decreased significantly